Comparison of nonspecific inflammatory markers in endometrial cancer and hyperplasia - Alper,Ezgi Ceren Dallı (2021)
SUMMARY OBJECTIVE: This study aims to analyze inflammatory markers among patients with endometrial cancer, hyperplasia with atypia/endometrial intraepithelial neoplasia, hyperplasia without atypia, and normal controls, thus observing the stage at which inflammation becomes the most significant. METHODS: A total of 444 patients who had endometrial sampling were included in the study (endometrial cancer, n=79; endometrial hyperplasia with atypia/endometrial intraepithelial neoplasia, n=27; endometrial hyperplasia without atypia, n=238; and normal controls, n=100). Neutrophil count, lymphocyte count, platelet count, platelet distribution width, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, CA-125, and endometrial thickness of the patients were recorded. RESULTS: Comparing the groups for neutrophil count, the hyperplasia with atypia group had higher values compared with both the hyperplasia without atypia group and the control group (p=0.003). When compared for the lymphocyte count, the hyperplasia with atypia group had lower values compared with the control group (p=0.014). Neutrophil/lymphocyte ratio of the hyperplasia with atypia group was higher than all other groups, and neutrophil/lymphocyte ratio of the cancer group was higher than the control group (p=0.001). Platelet count, mean platelet volume, platelet distribution width, and platelet/lymphocyte ratio values were not significantly different among groups (p>0.05). CONCLUSIONS: Considering the inflammatory markers, the most prominent result was that the hyperplasia with atypia group had neutrophilia, lymphopenia, and increased neutrophil/lymphocyte ratio compared with other groups.